What happened to and in Detroit?. (December 2014) - McDonald, John F
The paper describes the fiscal status of the city of Detroit leading up to its filing for bankruptcy on 18 July 2013. Then the economic history of metropolitan Detroit and the city of Detroit from 1950 to the present is examined in an effort to answer these questions: Why did Detroit file for bankruptcy – not some other major city? And why now and not earlier? The paper concludes that, while Detroit and several other cities in the northeastern region suffered major population and employment losses and went through a long period of urban crisis between roughly 1970 and 1990, the severity of Detroit's problems compared with other cities did not emerge fully until the most recent decade.